Portrait of a pathogen: a characterisation of mycobacterium tuberculosis and its host using multi-dimensional proteomics. - Gallant, James Luke (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.